Charity begins at home: The political economy of non-tariff barriers to trade in Southern Africa - Tracy Ledger (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2019)
Increased intra-regional trade in southern Africa will have a positive impact on economic growth. However, this requires a shifting of loyalties from the national to the regional. Tension between the goals of long-term regional development and shorter-term national imperatives remains unresolved. This study presents a review of recent and current local content regulation (LCR) initiatives across a sample of the South African Development Community countries. LCRs are widely used across these countries, and their use has increased recently. Evidence suggests that the impact of LCRs is mixed, depending on their national context, whether or not they are implemented in line with the genuine desire to deliver local development, and whether they can remain corruption-free. LCRs may have long-term positive domestic and regional benefits, if they support sustainable local enterprise development and employment. In time this should translate into higher levels of growth across the region, and thus drive higher levels of trade.
Keywords: F1; K3; L5; O2; 330; local content; regional integration; South African Development Community